The rise of reformist strongman: statutory executive aggrandizement and performative legitimacy in decentralized Indonesia - Aditya Putra; Muh. Farid; Muh. Akbar; Andi Alimuddin Unde (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
This study examines a key paradox in decentralization in Southeast Asia: the emergence of strong local figures who drive policy innovation while simultaneously consolidating executive power. Focusing on the city of Parepare, Indonesia, during the 2018–2023 period, this study addresses the urgent need to explain how decentralized governance can simultaneously enable reform while undermining democratic accountability. Based on qualitative case studies, this article introduces the concept of the mayor’s entrepreneurial mechanism, understood as a form of sequential entrepreneurship in which a mayor moves from narrative framing toward policy institutionalization. Findings show that this mechanism operates through the expansion of executive power based on legislation, where the autonomy mandate is used to centralize administrative authority, as well as through political co-optation that neutralizes legislative oversight. This study contributes to the governance and decentralization literature by demonstrating that reformist executive dominance may accelerate local development, yet also erodes the system of checks and balances. This tension raises critical concerns regarding the democratic sustainability of decentralized governance in Indonesia and the broader region.